Keperawatan Bencana: Pengurangan Risiko Bencana Tsunami melalui Komunitas Mangrove - Putra Agina Widyaswara Suwaryo; Sarwono Sarwono; Podo Yuwono (JHeS (Journal of Health Studies), 2021)
Disaster risk reduction needs to involve various parties, such as the community, certain institutions and organizations and the government. Mangrove-related studies prove that they can make a high contribution to becoming a natural fortress from the tsunami. The purpose of this study was to determine the plan, implementation and role of nurses in disaster nursing for tsunami risk reduction. This study uses a qualitative design. The data collection process used interviews and Focus Group Discussion (FGD) of 5 participants consisting of medical personnel namely nurses and lay people. The role of nurses in tsunami risk reduction as leaders, educators, responders, and assisting in communication in making policy with the government